PENGARUH KEPUASAN KERJA, PELATIHAN, DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP SERVICE ORIENTED-ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Habibullah Al Amnur; Syahrizal Syahrizal; Okki Trinanda (Universitas Negeri Padang, 2019)
The purpose of this study was to determine the effect of job satisfaction, training and Perceived Organizational Support on Service-Oriented Organizational Citizenship Behavior in Hotel Employees in the City of Padang. This type of research is descriptive causative. This research was conducted in the city of Padang. While the time of the study was conducted in 2018. The population in this study were 4-star hotel contract employees in the city of Padang with a sample of 106 people taken by cluster random sampling. Data is processed using multiple linear regression. The results showed that job satisfaction has a significant positive effect on service-oriented organizational citizenship behavior, training has a significant positive effect on service-oriented organizational citizenship behavior, perceived organizational support has a significant positive effect on service-oriented organizational citizenship behavior.Keywords : Service-Oriented Organizational Citizenship Behavior, Job Satisfaction, Training, Perceived Organizational Support